Postpartum Care Utilization among Medicaid-Insured Birthing People with an Infant Hospitalized in the NICU - Ondusko, Devlynne S.; Mazziotti, Julianna; Martinez Acevedo, Ann; Daly, Ashley; Rodriguez, Maria I. (American Journal of Perinatology, 2025)
This study aimed to determine the association of neonatal intensive care unit (NICU) admission with subsequent postpartum care among Medicaid recipients.Retrospective cohort study using linked Medicaid claims and birth certificate data from Oregon and South Carolina, 2010 to 2020. Outcomes were postpartum care attendance, contraception, emergency department (ED) utilization, and readmission. Linear regression models evaluated the association between NICU admission and postpartum care.Our sample included 457,102 birthing people, 37,035 (8.1%) of which had a NICU-admitted infant. Medicaid recipients with NICU-admitted infants had higher rates of cesarean section, pregnancy complications, postpartum mental health conditions, and substance use. No significant differences in postpartum care attendance were noted, but NICU admission was associated with 6% greater ED use (95% CI: 0.052, 0.068, p < 0.001) and 3% higher readmission (95% CI: 0.026, 0.034, p < 0.001).Postpartum care receipt was similar, but ED and readmission rates are higher among those with NICU-admitted infants. Preventative postpartum care approaches must improve for at-risk populations.
Keywords: postpartum care; NICU; disparities; health services